Controlled poling of a fully printed piezoelectric PVDF-TrFE device as a multifunctional platform with inkjet-printed silver electrodes. Issue 32 (26th July 2022) - Alique, Marc; Moya, Ana; Kreuzer, Martin; Lacharmoise, Paul; Murillo, Gonzalo; Simao, Claudia Delgado
Abstract : A novel all-printed piezoelectric device and its preparation methodology is presented as a multifunctional device platform with controllable polarization of the PVDF-TrFE layer, reversibly switching between piezoelectric and non-piezoelectric states. Abstract : Fully printed piezoelectric devices are important components for seamlessly integrated circuits. Herein, for the first time, inkjet-printed silver electrodes on a screen-printed PVDF-TrFE polymer on a flexible film are reported. Studies on different inks and printing conditions are performed to select and prepare bottom and top inkjet-printed electrodes on the screen-printed PVDF-TrFE layer. Thermal-assisted electrical poling and unpoling conditions for the device are obtained, with high reproducibility and reversibility in multiple cycles. The fully printed device is investigated as a sensor, an actuator, and an energy harvester as a single device multifunctional platform. A maximum output voltage of 3.6 V is achieved in piezoelectric devices when used as a vibrational sensor. The maximum output power of 1.6 μW with a 1.1 MΩ optimum load resistor was obtained when clamped as a cantilever and accelerated at 0.75 G and characterized as a microgenerator.